The Chinese Repository and Chinese Criminal Law in the Minds of Westerners of the 19th Century - Xiuqing Li (Rechtsgeschichte - Legal History, 2014)
The Chinese Repository was the first well-established comprehensive English language journal in China. Based on the exploration of The Chinese Repository, the article provides a general view and an analysis of the contents concerning the Chinese criminal law and other relevant information published thereon, summarizing the views of Chinese criminal law held by the Westerners of the 19thcentury and elaborating on the accountability and causes of the final consequence. Typical Westerners’ views of Chinese criminal law were as follows: There are too many provisions on violent crimes, especially on homicides, and as for homicides, whether murders or manslaughters, a life for a life was always a principle to be followed and the perpetrator had to be executed, with only few exceptions to that rule. Since the purpose of criminal punishment was to penalize rather than correct or educate criminals, the punishments were severe and among them, capital punishment was widely employed to cruel effect. The abuse of extortion was widespread and unlawful extortion or torture was common though prohibited. Laws in China, including criminal laws, lacked certainty, which was not only due to the arbitrariness in lawmaking and law-amending, but also to the excessive degree of discretion conferred on local government officers and given to the practice of implication (Zhu Lian), which reveals a certain backwardness and cruelty. These nearly »backward and barbarian« or »bloody and cruel« views of Chinese criminal law, though somewhat correct, are partial and imaginary to certain extent. These views rooted in the minds of Westerners at that time partly owe to the language obstacles, partly to the influences of West-centrism, the ideology of racial superiority, and conflicts or different ideas between the Chinese and Western t raditional o r historical legal systems. The Chinese Repository was the main, though not the only, widespread media between China and the West, through which the Westerners’ views of Chinese criminal law undoubtedly spread far and wide.